The comparison of mayo herniorraphy and mesh repair for incisional hernias - Bülbüller, Nurullah; Do?ru, Osman; Pektaş, Bahattin; Ilhan, Y. Selim; Çetinkaya, Ziya; Kirkil, Cüneyt (Turkish Surgical Society, 2003)
There have been reports on high recurrence rates for repairing methods of incisional hernias with synthetic materials recently. We compared the results of mayo herniorraphy, a doublelayer musculofacial repair and prosthetic mesh repair for incisional hernias. 125 patients were operated for incisional hernia at Firat University General Surgery Department between 1994-2001. 80 of them were followed and the results were compared median follow up for mayo herniorraphy and mesh repair group were 24 (range between 7 and 91 months) and 27 (range between 3 and 84 months) months respectively. Nine of the patients were male (11%), and 71 were female (88%). Mayo herniorraphy was performed on 39 patients and mesh repair was performed on 41 patients. Mean defect area in mayo herniorraphy and mesh repair were 25±4.0 cm2 and 81±12.6 cm2 (mean±standart deviation) respectively. Five complications occured in mayo herniorraphy group. Eight complications occured in mesh repair group. Mesh had to be removed in one patient for infection. Three recurrences occured in both groups. Recurence rates were 7.6% in mayo herniorraphy group and 7.3% in mesh repair group. Mayo herniorraphy can be safely applied for incisional hernia repairs if the defect diameter is small and patient has no predisposing factor.
Insizyonel hernilerde mayo herniyorafi ve meş onariminin karşilaştirilmasi
Keywords: Incisional hernia; Mayo repair; Mesh